The Connectivity of the Resting Brain in Primary Open-Angle Glaucoma: A Systematic Review - Nikola Velkov; Sevdalina Kandilarova; Drozdstoy Stoyanov (Biomedicines, 2025)
Background/Objectives: Worldwide, glaucomas are the leading cause of irreversible blindness in adults. On the ocular level, they are fairly well understood; however, the functional and structural changes that occur in the brain have become a subject of great interest lately, mostly owing to improved accessibility and effectiveness of functional magnetic resonance imaging (fMRI). This, coupled with the non-invasive nature of the methodology, has contributed to an ever-growing body of research published on the topic. In this systematic review, we gather, systematize, and compare the results and methodologies reported in the literature, as pertaining to resting-state fMRI brain changes in primary open-angle glaucoma (POAG). Methods: A systematic search in PubMed, Scopus, and Web of Science was carried out, resulting in a total of 290 records identified, with 67 assessed for eligibility and 24 selected for inclusion. Results: The main findings include worse functional parameters in the early visual centers in POAG across all methodologies, reduced functional connectivity between V1 and other parts of the visual cortex, functional aberrations in higher levels of the visual system, predominantly in the ventral stream and in extravisual networks, among others. Moreover, the majority of these changes are shown to be correlated with ophthalmological measurements. Conclusions: Although studies on this matter tend to suffer from a limited sample size and a lack of methodological standardization, we nevertheless manage to present common results and conclusions regarding the effects of POAG on brain function.